Multipliers from a Major Public Sector Relocation: The BBC Moves to Salford - Max Nathan; Henry Overman; Capucine Riom; Maria Sanchez-Vidal (Institute of Labor Economics (IZA), 2024)
This paper considers the impact of a major public sector relocation: the British Broadcasting Corporation's partial move from London to Salford, Greater Manchester starting in 2011. We identify effects of the move using synthetic control methods applied to plant-level data at Local Authority and Travel to Work Area level. Each BBC job creates on average 0.33 additional jobs in the creative industries, rising to 0.55 additional jobs by 2017, and the relocation had an impact on sectoral and firm composition. We find no significant effect on total employment but a small positive effect on Local Authority average wages.
Keywords: H70; R12; 330; cities; public employment; local multipliers; relocation; creative industries; policy evaluation